A meta-analysis on the association of ACE and PPARA gene variants and endurance athletic status - Ipekoglu, G.; Bulbul, A.; Cakir, H. I. (The Journal of Sports Medicine and Physical Fitness, 2022)
INTRODUCTION: Genetics has an important role in determining the athletic ability and endurance performance potential. This study aimed to investigate the variable results obtained from endurance athletes and control participants in terms of angiotensin-converting enzyme (ACE) and peroxisome proliferator-activated receptor alpha (PPARA) polymorphism distributions. EVIDENCE ACQUISITION: Multiple electronic databases were investigated independently by two researchers. A meta-analysis was conducted on the association of ACE insertion/deletion (I/D) polymorphism and PPARA G/C polymorphisms with endurance athletes. Odds ratios (OR) and 95% confidence intervals (CI) were estimated. Twenty-six studies were identified for the ACE I/D for 2979 endurance athletes and 10048 control participants while seven studies were identified for PPARA G/C for 901 endurance athletes and 2292 control participants. EVIDENCE SYNTHESIS: There was a significant difference in ACE genotype distribution between endurance athletes and control (II vs. ID+DD: OR=1.48; 95% CI=0.30-2.67; P=0.001). On the other hand, there was not a significant difference in PPARA G/C polymorphism genotype distribution between endurance athletes and control (GC+CC vs. GG: OR=0.93; 95% CI=-0.46-2.32; P=0.192; GC+GG vs CC: OR=0.62; 95% CI=-1.75-2.99; P=0.604). CONCLUSIONS: The results have shown that ACE I/D polymorphism may be associated with endurance performance in sports and that the predominance of the ACE II genotype in a person may play an advantageous role in being an endurance athlete. However, this effect has not been observed in PPARA G/C polymorphism.